A Remarkable Woman in African Independent Churches: Examining Christina Nku’s Leadership in St John’s Apostolic Faith Mission - Kgatle, Mookgo Solomon (Studia Historiae Ecclesiasticae, 2019)
The name African Independent Churches (AICs) refers to churches that have been independently started in Africa by Africans and not by missionaries from another continent. There has been extensive research on (AICs) from different subjects in the past. There is, however, a research gap on the subject of leadership in the AICs, especially with reference to women leaders. To address this gap, this article discusses leadership in the AICs with special reference to the leadership of Christina Nku in St John’s Apostolic Faith Mission (AFM). A historical examination of Christina Nku’s leadership is studied by looking at her roles as a family woman, prophet, church founder, faith healer and educator in St John’s AFM. The aim of this article is twofold. First it is to reflect on gender in the leadership of the AICs. Second it is to apply the framework of leadership in the AICs to Christina Nku’s leadership in St John’s AFM. Consequently, the article is an interface between gender and leadership in an African context. The purpose of this article is to demonstrate that Christina Nku was a remarkable woman in the leadership of the AICs.